Determination of Fatigue Life and Failure Location of Vehicle Cylindrical LPG Fuel Tanks - Kisioglu, Y.; Kartal, F. (Walter de Gruyter GmbH, 2016)
Abstract This study addresses the determination of the fatigue life and its failure locations of the vehicle cylindrical LPG fuel tanks using both experimental and finite element analysis (FEA) methods. The experimental investigations performed as an accelerated fatigue tests are carried out using a hydraulics test unit in which the cylinders are internally pressurized by hydraulic oil. The LPG cylinders are subjected to repeated cyclic pressure varying from zero to service pressure of the tank. The FEA modeling of these tanks are developed in three dimensional (3D) using non-uniform geometrical parameters and nonlinear material properties. These models are also subjected to zero-based high cycle fatigue pressure load considering the stress life approach. The FEA modeling process is also simulated in non-homogeneous material conditions. Therefore, the fatigue life performance and failure location of the cylindrical LPG fuel tanks are predicted and compared to the experimental results.
Keywords: 7. Clean energy